PENDAMPINGAN SISWA SMA PADA PEMELIHARAAN DAN PERBAIKAN INSTALASI LISTRIK DI SEKOLAH - I Ketut Perdana Putra; Ni Made Seniari; I Made Ginarsa; Supriyatna Supriyatna; Sabar Nababan; Bagus Widhi s (Jurnal Bakti Nusa, 2026)
Community service activities are one of the implementations of the Tri Dharma of Higher Education. Community service aims to improve the knowledge and skills of SMAN 10 Mataram students in maintaining and repairing simple electrical installations safely and in accordance with PUIL standards. The challenges faced by partners are students' limited understanding of electrical safety, installation inspection techniques, and basic skills in maintaining electrical installations in the school environment. The implementation method of the activity includes training in basic electrical installation theory, hands-on practice of installation inspection, and assistance in maintenance and repair of simple electrical installations. The activity participants involved 33 students of SMAN 10 Mataram consisting of grades X and XI. The results of the activity showed an increase in the ability to identify minor electrical installation damage, as well as the skills to carry out simple repairs independently with assistance. This activity has a positive impact, namely increasing awareness of electrical safety and technical skills in electrical installations for students as basic provisions in everyday life.